2022
DOI: 10.1186/s12885-022-09972-9
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for the micropeptide encoded by LINC02381 regulates ferroptosis through the glucose transporter SLC2A10 in glioblastoma

Abstract: Glioblastoma (GBM) is the most common primary intracranial tumor in the central nervous system, and resistance to temozolomide is an important reason for the failure of GBM treatment. We screened out that Solute Carrier Family 2 Member 10 (SLC2A10) is significantly highly expressed in GBM with a poor prognosis, which is also enriched in the NF-E2 p45-related factor 2 (NRF2) signalling pathway. The NRF2 signalling pathway is an important defence mechanism against ferroptosis. SLC2A10 related LINC02381 is highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…We then validated our findings using qPCR experiments and spatial transcriptome data. Among these SLCs, SLC2A10 has been reported to be associated with ferroptosis in glioblastoma, 43 SLC47A1 has been demonstrated to mediate temozolomide resistance in glioblastoma, 44 while the functions of the other SLCs in glioblastoma remain unclear. Next, to enhance the prediction of prognosis for glioma patients, we established a risk scoring system based on these seven core SLCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then validated our findings using qPCR experiments and spatial transcriptome data. Among these SLCs, SLC2A10 has been reported to be associated with ferroptosis in glioblastoma, 43 SLC47A1 has been demonstrated to mediate temozolomide resistance in glioblastoma, 44 while the functions of the other SLCs in glioblastoma remain unclear. Next, to enhance the prediction of prognosis for glioma patients, we established a risk scoring system based on these seven core SLCs.…”
Section: Discussionmentioning
confidence: 99%
“…to be associated with ferroptosis in glioblastoma, 43 In fact, our risk scoring system, which is based on the product of regression coefficients and expression levels, quantifies the distinct expression patterns of these seven SLCs in different patients.…”
Section: The Distinctive Contribution Of Slc43a3 To Risk Scoring and ...mentioning
confidence: 99%
“…Interestingly, Jiang et al found that LINC02381-aa, a micropeptide encoded by LINC02381, localizes to exosomes and may regulate iron concentration in GBM via the action of the glucose transporter SLC2A10 [ 114 ]. Furthermore, it was found that exosomal lncAKR1C2 can encode a microprotein with biological functions in recipient cells and promotes the expression of CPT1A by regulating YAP phosphorylation, which leads to enhanced fatty acid oxidation and ATP production.…”
Section: Tumour-associated Micropeptides Localize To Different Subcel...mentioning
confidence: 99%
“…In GBM, LINC02381 is highly expressed and localized in the cytoplasm, whereas its coding micropeptide is enriched in the exosome and promotes cell proliferation and growth by regulating ferroptosis. LINC02381‐aa 89 interacts with SLC2A10 and activates the NRF2 signaling pathway, which plays an important role in defending against ferroptosis. Furthermore, the presence of LINC02381‐aa in exosomes can be a potential antitumor therapy for targeting exosomes (Figure 3H).…”
Section: Subcellular Localization Of Micropeptides and Related Mechan...mentioning
confidence: 99%